Impact of Digital Financial Inclusion (DFI) Initiatives on the Self-Help Group: For Sustainable Development - Mahesh K. M.; Aithal P. S.; Sharma K. R. S., (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: India has been the advocate the digital infrastructure addressing last-mile connectivity through financial inclusion by integrating innovative financial technology(fintech)and Digital Ecosystem for making financial services more accessible to a large number of people, at present India’s fin tech adoption rate is 87% in the world, Digital ecosystem will account for 30% of global revenues by 2025 as per McKinsey and Digital Financial Services(DFS) is a tool to boost the inclusive growth and access to the finance for solving societal issues and economic growth by adaption of SHG, JLG and Farmer Interest Groups(FIGs) in Farm and Non-Farm Sector and digital model more impact in creating micro-entrepreneurs in non-agriculture sector, employment in Sustainable agriculture, reducing poverty, income equality, equitable society with good health and wellbeing and economic growth with initiatives undertaken by the current government to improve financial inclusion in association with RBI, NABARD, NBFC in Empowering the sustainable development goals and more opportunities for women in rural areas as well as tire 3,tiere4 cities in improving lives with the Financial inclusion initiatives like the National Strategy for Financial Inclusion (NSFI), NABARD E – Shakti, Pradhan Mantri Jan Dhan Yojana (PMJDY), Atal Pension Yojana, Pradhan Mantri Suraksha Bima Yojana, Bharat Interface for Money (BHIM), Electronic Benefits Transfer (EBT)/Direct Benefit transfer, JAM, e-KYC, smart panchayats, agriculture credit, Buy Now Pay Later(BNPL), Digital Banks, Central Bank Digital Currency(DBDC), Robotic Automation with AI, Block chain Technology, Neo banks, Kisan Credit. The innovations and revolution that have had the biggest effect on inclusive digital and financial services include BSB for MSMEs, Rupay, Paytm, PhonePe, Google Pay, and Bharat Interface for Money (BHIM), as well as cloud computing, biometrics, government e-marketplaces, AGMARKNET, and FPOs. RBI FINANCIAL INCLUSION INDEX2022 indicates a gap in FI in India and it impacts GDP, and Atmanirbhar Mahila - Aatmanirbhar Bharat. Design/Methodology: The research relies on secondary data, which were gathered from websites, journals, newspapers, magazines, reports, and Case studies on SHGs promoted by SKDRDP-Shri Kshetra Dharmasthala Rural Development Project. The data are descriptively analysed. Originality/value: Digital Financial Inclusion (DFI) Initiatives on The Self-Help Group: For Sustainable Development and its impact studied through various case studies- how it is helpful to self-help groups. Paper type: Conceptual framework